2020
DOI: 10.1083/jcb.202001122
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas PKD2 organizes mastigonemes, hair-like glycoprotein polymers on cilia

Abstract: Mutations in the channel protein PKD2 cause autosomal dominant polycystic kidney disease, but the function of PKD2 in cilia remains unclear. Here, we show that PKD2 targets and anchors mastigonemes, filamentous polymers of the glycoprotein MST1, to the extracellular surface of Chlamydomonas cilia. PKD2–mastigoneme complexes physically connect to the axonemal doublets 4 and 8, positioning them perpendicular to the plane of ciliary beating. pkd2 mutant cilia lack mastigonemes, and mutant cells swim with reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 68 publications
4
68
0
Order By: Relevance
“…These may be localized to cilia and flagella, which display an active load response [ 137 , 138 ]. Hair-like extensions of cilia (mastigonemes) are also implicated in mechanosensing in Chlamydomonas [ 139 ]. A combination of rheosensing and chemosensing guides sperm motility through the mammalian oviduct.…”
Section: Forms Of Excitability In Eukaryotesmentioning
confidence: 99%
“…These may be localized to cilia and flagella, which display an active load response [ 137 , 138 ]. Hair-like extensions of cilia (mastigonemes) are also implicated in mechanosensing in Chlamydomonas [ 139 ]. A combination of rheosensing and chemosensing guides sperm motility through the mammalian oviduct.…”
Section: Forms Of Excitability In Eukaryotesmentioning
confidence: 99%
“…Chlamydomonas PKD2 localises to the flagella membrane, but is also bound to the axoneme and to extracellular glycoprotein polymers known as mastigonemes that resemble hair-like appendages along the distal regions of the flagella 49,50 . The tethering of PKD2 to mastigonemes and the axoneme supports a mechanosensory role in Chlamydomonas 50 .…”
Section: Discussionmentioning
confidence: 99%
“…can occur within seconds even within individual cells 22 . The pkd2 mutants' lack of mastigonemes, indicates that ion channel mutants may influence the arrangement of flagella glycoproteins 50 . Whilst mastigonemes are not thought to be involved in microsphere movements or gliding motility 51,52 , it is clear that knockout of an ion channel could influence the processes that trigger [Ca 2+ ]fla elevations (i.e.…”
Section: Gliding Motility Is Often Markedly Different Between Strainsmentioning
confidence: 99%
“…Electrophysiological and structural studies have revealed that most polycystins are calcium-permissive cation channels closely associated with the primary cilium (Gonzalez-Perrett et al, 2001; Hanaoka et al, 2000; Liu et al, 2018; Su et al, 2018), but their functions have turned out to be surprisingly diverse. While the fruit fly and worm polycystins are essential for the male fertility (Barr and Sternberg, 1999; Watnick et al, 2003), it plays a non-essential structural role in the cilium of green algae Chlamydomonas reinhardtii (Huang et al, 2007; Liu et al, 2020; Wood et al, 2012). In comparison, the polycystin homologue of social amoebae Dictyostelium discoideum contributes to cell locomotion (Lima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, their functions have turned out to be surprisingly diverse. While the fruit fly and worm polycystins are essential for male fertility (Barr and Sternberg, 1999; Watnick et al, 2003), the polycystin of the green algae Chlamydomonas reinhardtii plays a non-essential structural role in the cilia (Huang et al, 2007; Liu et al, 2020; Wood et al, 2012). In comparison, the polycystin homologue of social amoebae Dictyostelium discoideum contributes to cell locomotion (Lima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%